Amine‐modified graphene enhanced mechanical properties and catalytic effect on imidization of polyimide composite films. Issue 12 (5th October 2022) - Zhao, Yuzhuo; Hu, Yanbing; Zhang, Shaopeng; Wang, Song; Zhang, Ailing; Liang, Bing; Li, Sanxi
Abstract: The degree of the imidization reaction determines the properties of polyimide (PI) obtained by the thermal curing process. In this paper, amine‐modified graphene (N‐GO) was designed by integrating pyridine structure with graphene and acting as a catalyst to promote the imidization reaction of PI. Fourier‐transform infrared spectroscopy (FTIR), scanning electron microscope (SEM) were then used to confirm the morphology and structure of N‐GO. The catalytic effect of N‐GO in imidization reaction was obtained by FTIR and subsequently characterized by differential scanning calorimetry (DSC) and water contact angle (WCA). Surprising results suggest that the agglomeration of N‐GO can also contribute to solid‐phase reactions in imidization reactions. Lastly, the results of mechanical property tests, thermogravimetric analysis (TGA), and FTIR demonstrated that the composite films showed excellent tensile strength (176.2 MPa) and thermal stability (513.0 °C); at the same content, only 0.5% of N‐GO addition reduced the imidization temperature by 20°C, exhibiting remarkable enhancement effects. This research is a valuable solution to the problem in performance caused by low‐temperature curing agent residues in films, and it is expected to be used in the microelectronics field. Abstract : We explore a new strategy to catalyze the imidization of polyimide by synthesizing amine‐based graphene containing pyridine structure using water as a solvent. It was found that the amine‐modified graphene showed a remarkable effect in mechanical properties and catalytic effects; in addition, the agglomeration caused by excess graphene also promoted thermal imidization.